Kearifan Lokal Pemanenan Madu Hutan Masyarakat Desa Muara Ripung Kecamatan Dusun Selatan Kabupaten Barito Selatan - Eko Pranandhita; Sidik Rahman Usop; Hendrik Segah (Program Pascasarjana Universitas Palangka Raya dan (and) Ikatan Ahli Teknik Penyehatan dan Teknik Lingkungan Indonesia (IATPI), 2020)
Forest honey is widely known as non-timber forest products (NTFPs) with high economic value and contains many beneficial substances for human body. Forest honey in several villages in South Barito district has been managed traditionally. This study aims to describe the processes of forest honey cultivation and the application of local wisdom values in a group of honeybee farmer in Muara Ripung Village, South Barito. A qualitative measurement through in-depth interview and field observations were applied in data collection and analysis. The results show that forest honey management helps to sustain forest area since forest is essential to support the availability of honey nest and bees feed. In addition, farmers also still use traditional harvesting tools and procedures as did by their predecessors.